Final Results of the EORTC Intergroup Randomized Phase 3 Study 40983 Evaluating the Benefit of Perioperative FOLFOX4 Chemotherapy for Patients with Potentially Resectable Colorectal Cancer Liver Metastases - Helwick, Caroline (MD Conference Express, 2007)
Perioperative chemotherapy provided benefit for patients with colorectal cancer who were treated with surgery for potentially resectable liver metastases. This article discusses the final Results of the EORTC Intergroup Randomized Phase 3 Study 40983 evaluating the benefit of perioperative FOLFOX4 chemotherapy for patients with potentially resectable colorectal cancer liver metastases.